Intensitas Penerapan Strategi Mitigasi Kekeringan di antara Rumah Tangga di Sub-Kabupaten Tharaka Selatan, Kenya - Mukami, Nyaga Mary; Njeru, Moses Kathuri; Njue, Paul Nyaga (PT. Pubsains Nur Cendekia, 2025)
Recent uncertainties in rainfall amount and intensity have increased drought. This situation has prompted the need to assess the intensity of the adoption of the drought mitigation strategy. This study analyzed ten drought mitigation strategies (DMS) among households using the descriptive statistical approach in Tharaka South Sub-County, Kenya. About 397 samples from 18,623 households and 3 key informants were selected as informants. They were selected using cluster random sampling and purposive sampling, respectively. Data collection was done through questionnaires, interviews, and observations. The study revealed that planting drought-tolerant crops (89.7%), crop diversification (84.2%), and rainwater harvesting (78.1%) were among the top three widely adopted DMS for drought mitigation. Community programs (23.2%), irrigation (15.1%), and soil conservation (6.1%) had low adoption among households. The households are more likely to adopt simple strategies. Therefore, policy support is needed for less implemented strategies, such as soil conservation and irrigation.